ADAPTASI PEDAGANG PASCA KEBAKARAN DI TEMPAT PENAMPUNGAN SEMENTARA (TPS) PLAZA SUKARAMAI KOTA PEKANBARU - Muhammad Suheil; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was carried out at Plaza Sukaramai Pekanbaru. With the formulation of the problem (1) how is the ability to adaption the Sukaramai plaza traders after the fire at the Plaza Sukaramai Pekanbaru temporary shelter? (2) what are the factors that influence the ability of adaptation of merchant Plaza Sukaramai Pekanbaru at the Temporary Shelter Plaza Sukaramai Pekanbaru ?. The purpose of this study is to find out how the traders adaptation capabilities, and to determine the factors that affect the ability of adaptation of traders Plaza Sukaramai after the fire. This research is a descriptive research with a strongitative approach. The population in this study as much as 1060 traders and then used one sampling technique proportional sampling then in get a sample of 106 respondents scattered in several blocks, to collect data in this study used questionnaires and documentation. Based on the results of the above research can be concluded that (1) of the 5 indicators tested by crosstabulation by using spss 17.0 in get the results of the adaptation level of traders in shelters While belonging to the high category (2) of the 6 factors that affect the ability the adaptation of traders in the temporary shelter of Plaza Sukarami from 106 respondents there are 78 respondents who agreed agreed with the percentage of 73.6% to the discounted price, 79 respondents with 74.5% percentage apply the cheap price, Number of kiosk there are 68 respondents agreed with percentage 83.0%, and service there are 88 respondents with percentage of 83.0% and the most influential factor. The relationship between the level of adaptation ability of traders in place in the Temporary Shelter and factors affecting the level of adaptation of traders in the Temporary Shelter of 0.860 (86.0%) relationships are strong, it can be stated that Ha received that there is a relationship between the level of adaptability with the factors affects the level of adaptability is quite strong.Keywords: adaptation,traders